Proceedings of China modern logistics engineering inheritance, wisdom, innovation and cooperation (Springer Berlin Heidelberg, 2015)
Proceedings of China Modern Logistics Engineering covers nearly all areas of logistics engineering technology, focusing on the latest findings and the following theoretical aspects: Logistics Systems and Management Research; Green Logistics and Emergency Logistics; Enterprise Logistics; Material Handling; Warehousing Technology Research; Supply Chain Management; Logistics Equipment; Logistics Packaging Technology; Third-party Logistics, etc. The book will help readers to grasp the relevant aspects of the theory involved, research and development trends, while also offering guidance for their work and related studies. It is intended for researchers, scholars and graduate students in logistics management, logistics engineering, transportation, business administration, E-commerce and industrial engineering.